Pengaruh Eksistensi Kelompok Tani terhadap Pendapatan Anggota dalam Perspektif Ekonomi Islam (Studi Kasus: Kelompok Tani Aceh Saiyo, Nagari Batupalano) - Riri Anjas Mita; Ariyun Anisah (Lembaga Yasin AlSys, 2026)
The existence of farmer groups plays an important role in supporting agricultural economic activities and increasing members’ income, especially when managed based on Islamic economic principles. Although the theme of farmer groups has been examined in various studies, research specifically discussing the effect of the existence of farmer groups on members’ income from the perspective of Islamic economics in Nagari Batupalano remains limited. This study aims to analyze the effect of the existence of farmer groups on increasing members’ income from the perspective of Islamic economics. This study used a quantitative approach with a survey design, involving members of farmer groups as respondents selected through purposive sampling. Data were collected through questionnaires, interviews, and observation, and were then analyzed using simple linear regression with the assistance of SPSS 26. The results showed that the existence of farmer groups had a positive and significant effect on members’ income, with a calculated t-value of 24.219, which was greater than the t-table value of 1.997, and a significance value of 0.000. The coefficient of determination (R²) value of 0.90 indicated that 90% of the variation in members’ income was explained by the existence of farmer groups. The conclusion of this study affirms that the activity and institutional function of farmer groups play an important role in increasing members’ income. These findings contribute to the development of studies on agricultural institutions and Islamic economics, particularly regarding the application of the values of justice, ta’awun, and amanah in community economic activities. The implications of this study indicate the importance of strengthening member participation, organizational governance, and government support in making farmer groups a means of community economic empowerment.